Inconsistency in the Formulation of Article 2 and Article 3 of Law No. 31 of Corrupt Practices Eradication Law and Disparity in Criminal Penalty for Mining Corruption in the Practice of Law Enforcement - Suastuti, Eny; Minarno, Nur Basuki; Sufyan, Akhmad Farid Mawardi; Poernomo, Gatoet (Journal of Law and Legal Reform, 2025)
This research discusses the transformation of understanding and law enforcement of the elements of Article 2 and Article 3 of the Corruption Eradication Law. The element against the law is Article 2 of the Corruption Eradication Law. In contrast, the element of abuse of authority is the core of the offense in Article 3 of the Corruption Eradication Law. Thus, it is inappropriate to indict the perpetrators of mining corruption with an alternative form of indictment between Article 2 and Article 3 of the Corruption Eradication Law. Inconsistencies in formulating the elements of the offense and the parameters of the article have resulted in disparities in punishment, errors in assessing the existence of abuse of authority by using unlawful parameters and mixing the application of the two articles. This can be viewed in several Supreme Court Decisions in mining corruption cases, where the elements and subjects of the offense are interchangeable. This research aims to study the inconsistent formulation of the elements of the offense in Article 2 and Article 3 of the Corruption Eradication Law, which has led to disparities in punishment in mining corruption cases. This study is conducted by analyzing several Supreme Court Jurisprudence. This research employs normative research with a statutory approach, concept approach, and case approach. The results of this study aim to provide a recommendation on the concept of against the law and abuse of authority in the Corruption Eradication Law.